Association Between Lipid Profile and Prognostic Scores in Cirrhotic Patients - Abdul Jabbar, Rashed Ali Khan, Nazia Israr, Momin Khan, Muhammad Yaqoob Khan, Irshad Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cirrhosis is a high morbidity and mortality severe progressive liver disease. Dyslipidemia is a common finding among patients with cirrhosis, but the association between dyslipidemia and prognostic scores has not been well investigated. Lipid abnormalities can be conceptualized to shed some light on the course and outcome of diseases. Objective: The purpose of the study is to examine the association between the lipid profile abnormalities (HDL, LDL, triglycerides) and prognostic scores (MELD, Child-Turcotte-Pugh) of patients with cirrhosis. Methods: The study was a prospective observational study involving 100 cirrhotic patients from Medicine Department Saidu Group Teaching Swat, KPK from 1st November, 2022 to 30th April, 2023. The prognostic scores (MELD and Child-Turcotte-Pugh) and lipid profiles (total cholesterol, HDL, LDL, and triglycerides) were measured. Correlation test and regression test were performed to determine the correlation between lipid profiles and the prognostic scores. Results: HDL had a strong negative association with MELD and Child-Turcotte-Pugh scores, and the triglycerides had a positive relationship. Low levels of triglycerides and high levels of HDL cholesterol were linked to poor outcomes. Conclusion: The low levels of HDL and high levels of triglycerides correlate with the poorer prognosis among cirrhotic patients, which means that they should be considered as prognostic biomarkers. Keywords: Cirrhosis, lipid profile, HDL, triglycerides, MELD, Child-Turcotte-Pugh, prognosis.